2022
DOI: 10.1177/20563051221129140
|View full text |Cite
|
Sign up to set email alerts
|

How Does Multi-Platform Social Media Use Lead to Biased News Engagement? Examining the Role of Counter-Attitudinal Incidental Exposure, Cognitive Elaboration, and Network Homogeneity

Abstract: Using an online panel survey in the United States, this study examines how multi-platform social media use impacts news engagement on social media. Results show that multi-platform social media use prompts incidental exposure to counter-attitudinal news and further encourages people to cognitively elaborate on the counter-attitudinal information, which in turn contributes to news engagement on social media. However, news engagement is performed in a biased way that is supportive of like-minded content and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Although one study noted that single-item measures are often as valid and reliable as their multi-item counterparts (Hoeppner et al, 2011), future studies could benefit from testing the scale’s convergent and concurrent validity. In addition, the observation that the average multi-platform social media use for news is 1.08, despite corroborating previous research (Chan et al, 2021b; Guo & Chen, 2022 M = 1~2), future studies could explore whether this varies across different devices or modalities. Finally, although comparative analysis is useful for making comparisons, causality may not be conclusively determined from cross-sectional data.…”
Section: Discussionsupporting
confidence: 80%
“…Although one study noted that single-item measures are often as valid and reliable as their multi-item counterparts (Hoeppner et al, 2011), future studies could benefit from testing the scale’s convergent and concurrent validity. In addition, the observation that the average multi-platform social media use for news is 1.08, despite corroborating previous research (Chan et al, 2021b; Guo & Chen, 2022 M = 1~2), future studies could explore whether this varies across different devices or modalities. Finally, although comparative analysis is useful for making comparisons, causality may not be conclusively determined from cross-sectional data.…”
Section: Discussionsupporting
confidence: 80%
“…For example, key users may demand that the production process and content of the videos is as rigorous and accurate as possible. Second, regulatory agencies must closely monitor health-related video content and prevent the dissemination of misleading videos on the internet [ 45 ]. Finally, relevant governments, professional organizations, and experts should proactively counter misinformation or disseminate quality health-related information on social media.…”
Section: Discussionmentioning
confidence: 99%
“…News elaboration is a cognitive process involved in processing news information, playing a critical role in comprehension (Guo & Chen, 2022). Individuals acquire understanding of using cognitive elaboration to analyze political topics from media.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Jakarta demonstrated that cognitive elaboration mediates the relationship between political persuasion and social media use (Venus et al, 2023). Individuals often read news in a way that confirms their pre-existing beliefs while rejecting arguments that contradict their opinions (Guo & Chen, 2022). According to Motivated Reasoning Theory, individuals exposed to information contradicting their beliefs tend to process biased information and critique arguments opposing their beliefs.…”
Section: Introductionmentioning
confidence: 99%